THE INFLUENCE OF PHENOMENON BASED LEARNING ON CREATIVE THINKING AND COLLABORATION SKILLS - Khusnul Khatimah; Adnan Adnan; A. Mu'nisa; Firdaus Daud; Nurhayati B (Universitas Labuhanbatu, 2026)
Purpose – This study aimed to investigate the effect of PhBL learning applied with three variations of PhBL (direct phenomenon, indirect phenomenon, and combined phenomenon) on students' creative thinking and collaboration skills.Methodology – This study used a quasi-experimental, pretest–posttest control-group design. Participants were drawn from all Grade XI students, with four classes serving as the research sample. Creative thinking skills were measured through open-ended questions, while collaboration skills were assessed via observation sheets administered before and after PhBL. The collected data were then analyzed using both descriptive and inferential statistical methods.Findings – Results revealed that PhBL affected creative thinking and collaboration skills. Although no significant differences were observed among the three experimental groups in creative thinking, each experimental group differed significantly from the control group. Similarly, for collaboration skills, experimental groups did not differ significantly from one another. However, significant differences from the control group were observed only in experimental groups 1 and 2, whereas experimental group 3 showed no significant differences.Contribution – This study shows that PhBL can be applied in the learning process to improve students' creative thinking and collaboration skills.